Does Reduced Dwelling Time Leads To Higher Tax Revenue? The Important Role Of Government Effectiveness In ASEAN-5 - Pascal, Emilio; Wijaya, Suparna (Educoretax, 2024)
This study aims to analyze the factors that affect tax revenue on international trade in ASEAN-5 countries. Data was obtained from The World Bank and analyzed using panel data regression. Variables used in this study are tax revenue on international trade, import growth, dwelling time, and government effectiveness. The results show that import growth, dwelling time, import growth that has been moderated by government effectiveness, and dwelling time that has been moderated by government effectiveness simultaneously affect tax revenue on international trade. Partially, import growth, dwelling time, and government effectiveness have a positive effect on tax revenue on international trade. However, when moderated by government effectiveness, import growth and dwelling time show a negative effect on tax revenue on international trade. The recommendation from this study is for the government to improve the quality of public services in the process of loading and unloading goods. Effective public services at ports and airports, balanced with efforts to reduce dwelling time, will increase tax revenue on international trade. The steps that the government can take are to simplify business processes at the port, for example, joint inspection between customs and quarantine authorities. In addition, the government needs to sterilize port and airport areas so that unauthorized parties do not hinder the flow of goods in and out. Public service improvements can also be made in other sectors because they have a significant impact on increasing tax revenue on international trades.